2020
DOI: 10.1109/temc.2019.2923101
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Currents on Fastening Assemblies of an Aircraft Fuel Tank, Part I: Uncertainties Assessment With Statistical Approach

Abstract: This paper proposes a statistical approach able to assess the fastening resistances uncertainties in aircraft assemblies. This method relies on the use of the maximum likelihood estimation method, several statistical tests and/or statistical criteria. Using the Dassault-Aviation measurement database, distribution laws are established in order to characterize uncertainties in the lightning impact on the fasteners. A simple FDTD fastener model is proposed with a wire and a resistance. This generic model can repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition, a damaged wire can adversely affect EMC and lead to EMI. Even though we avoid a detailed discussion, readers may refer to [138]- [140] for further study.…”
Section: F Wiring Harnessmentioning
confidence: 99%
“…In addition, a damaged wire can adversely affect EMC and lead to EMI. Even though we avoid a detailed discussion, readers may refer to [138]- [140] for further study.…”
Section: F Wiring Harnessmentioning
confidence: 99%
“…The inherent inaccuracy of their results is due to strong uncertainties about the contact resistances values. Indeed, it has been demonstrated that their variability is strong and has an important impact for the lightning current estimation [3], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed approach in [6], [7] is to merge an uncertainties model with a FDTD fastener model. A general method applied to the contact resistance uncertainties allows defining a probability law as uncertainties model [6]. This model represents the variability of the equivalent fastener resistance whatever the fastener type.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations